(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Before the COVID pandemic, solo travel was getting more and more popular – especially among women travelers. Both demographic, social trends, and inner motivations enhanced the popularity of this type of travel. The aging society and the single lifestyle increased the demand on the one hand, while on the other hand, the desire for self-realization, to find new ways of life, escapism, the thirst for self-confidence drive more tourists to travel alone. In the case of women travelers, their increasing decisive power and independence also boosted solo travel. The tourism industry also offers several attractions specially designed for them. The post-pandemic era will show how this special group of travelers will react to the changed circumstances and how they will change their travel habits. The paper examines how frequently Hungarian respondents travel alone and what their attitudes towards this type of traveling are.